Analisis Pengaruh Produk Domestik Regional Bruto (PDRB), Pengangguran, Inflasi, dan Indeks Pembangunan Manusia terhadap Tingkat Kemiskinan di 5 Kota Besar di Indonesia - Nuraini Chaniago; Muhamad Gibran Hernanda (ISLAMINOMICS: JOURNAL OF ISLAMIC ECONOMICS, BUSINESS AND FINANCE, 2022)
This study aims to analyze the effect of regional gross domestic product, unemployment, inflation, and the human development index toward poverty rate in 5 Big Cities in Indonesia. The research uses a panel data regression analysis model by utilizing the Eviews 9 analysis as a tool. The data is sourced from the Central Statistics Agency and other sources for the period 2010-2020. The results of this study indicate that after conducting the Chow and Hausman tests, the selected model is the Fixed Effect Model (FEM) which shows that gross regional domestic product has a negative and significant on the poverty level, On the other hand, the unemployment has a positive and no effect on the poverty level, inflation has a negative and no significant effect on the poverty level, and the human development index has a positive and no significant effect on the poverty level. Simultaneously, regional gross domestic product, unemployment, inflation, and human development index have significantly affected on the level of poverty in the 5 big cities in Indonesia.